2021
DOI: 10.3390/nano11112962
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Thick-Film Li(Ni0.6Mn0.2Co0.2)O2 Cathode with Hierarchic Structures and Laser Ablation

Abstract: The electrochemical performance of lithium-ion batteries is directly influenced by type of active material as well as its morphology. In order to evaluate the impact of particle morphology in thick-film electrodes, Li(Ni0.6Mn0.2Co0.2)O2 (NMC 622) cathodes with bilayer structure consisting of two different particle sizes were manufactured and electrochemically characterized in coin cells design. The hierarchical thick-film electrodes were generated by multiple casting using NMC 622 (TA) with small particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Our previous works displayed that the cells with laser patterned NMC electrodes exhibit high capacity retention after long-term cycling and show higher capacity at fast charge and discharge rates over C/2 in comparison to reference cells with unstructured electrodes. 8,14,15 , while other researchers observed similar phenomenon using other cathode materials such as LCO with line structures 16 , and LFP with hole structures 17 . Besides, laser patterned graphite-based anodes (with or without silicon) with lines, grids, and holes display high capability at elevated C-rates [18][19][20][21] .…”
Section: Introductionsupporting
confidence: 53%
“…Our previous works displayed that the cells with laser patterned NMC electrodes exhibit high capacity retention after long-term cycling and show higher capacity at fast charge and discharge rates over C/2 in comparison to reference cells with unstructured electrodes. 8,14,15 , while other researchers observed similar phenomenon using other cathode materials such as LCO with line structures 16 , and LFP with hole structures 17 . Besides, laser patterned graphite-based anodes (with or without silicon) with lines, grids, and holes display high capability at elevated C-rates [18][19][20][21] .…”
Section: Introductionsupporting
confidence: 53%
“…24,25 Since graphite anodes typically show higher diffusion limitations than most cathodes, electrode structuring is especially promising when applied to anodes. 26,27 Nevertheless, performance enhancements were also reported for LIBs containing structured LiMn 2 O 4 (LMO), 28 LiCoO 2 (LCO), 29,30 LiNi x Mn y Co z O 2 (NMC) [31][32][33] and LiFePO 4 (LFP) cathodes. 22,34 Additionally, it could be shown that the time-consuming electrolyte filling process, which largely contributes to the production costs of LIBs, 35 can be significantly accelerated through electrode structuring.…”
mentioning
confidence: 99%
“…Two redox peaks were observed within the range of 3.50 V to 4.02 V, indicating the presence of oxidation (Ni 2+ → Ni 3+ → Ni 4+ ) during charging and reduction (Ni 4+ → Ni 3+ → Ni 2+ ) during discharging. 17 By employing CV, the peak potentials for the anodic and cathodic sweeps can be identified, which are respectively known as E pa and E .…”
Section: Resultsmentioning
confidence: 99%